The Influence Of Creative Content And Influencers On Consumer Buying Interest (Case Study Of Bobby Syaputra Influencer On Instagram Application) - Akbar, Fikri; Naruliza, Esty; Emeila, Sri (Journal of Management, Economic, and Accounting, 2025)
Bobby Syaputra is a public figure on the Instagram platform who consistently shares promotional content for various products and brands. The primary objective of this study is to examine the impact of creatively designed content and Bobby’s personal influence as an Instagram influencer on consumer purchase intention—both simultaneously and individually. This study involved 272 participants selected from the followers of Bobby Syaputra's Instagram account, with a margin of error set at 10% or 0.1. The data collected is primary in nature, obtained through the distribution of digital questionnaires via Google Forms to followers who have been exposed to his promotional content. Data analysis was carried out using SPSS version 26, employing a series of tests including validity and reliability testing, classical assumption testing, and hypothesis testing. The findings reveal that the coefficient of determination (R²) is 0.535 or 53.5%, indicating that more than half of the variance in consumer purchase intention can be explained by the two main variables: creative content and influencer effect, while the remaining 46.5% is influenced by other variables not examined in this study. More specifically, creative content contributes 21.1%, while Bobby’s influence as an Instagram figure contributes 25.4% to consumer purchase intention. Thus, it can be concluded that both jointly and individually, engaging content and the presence of a trusted influencer have a significant and measurable effect on consumers’ intentions to make a purchase through Bobby Syaputra’s Instagram account. These results support the validity of the research hypotheses previously proposed. It has been proven that there is a positive correlation between creative content and influencer credibility in increasing consumer motivation to purchase promoted products.